Orthognathic Surgery after Mandibular Large-Volume Osteoma Treatment - Sabit Demircan; Sabri Cemil İşler; Aydın Gümüşdal; Begüm Genç (Case Reports in Dentistry)
Osteoma is a benign asymptomatic osseous tumor. Characterization of osteoma is the proliferation of cancellous or compact bone that increases in size by continuous formation of bone. It can be seen in any craniofacial structures, usually in paranasal sinuses and jaws. In this study, we present a 17-year-old male patient with a giant osteoma in the mandibular condyle. Posttreatment post-op follow-up, post-ortho, and orthognathic surgery after dental implantation are described.